Periodontal soft tissue root coverage procedures: A Consensus Report From the AAP regeneration workshop (2015)
Management of gingival recession defects, a common periodontal condition, using root coverage procedures is an important aspect of periodontal regenerative therapy. The goal of the periodontal soft tissue root coverage procedures group was to develop a consensus report based on the accompanying systematic review of root coverage procedures, including priorities for future research and identification of the best evidence available to manage different clinical scenarios. The group reviewed and discussed the accompanying systematic review, which covered treatment of single-tooth recession defects, multiple-tooth recession defects, and additional focused questions on relevant clinical topics. The consensus group members submitted additional material for consideration by the group in advance and at the time of the meeting. The group also identified priorities for future research. All reviewed root coverage procedures provide significant reduction in recession depth, especially for Miller Class I and II recession defects. Subepithelial connective tissue graft (SCTG) procedures provide the best root coverage outcomes. Acellular dermal matrix graft (ADMG) or enamel matrix derivative (EMD) in conjunction with a coronally advanced flap (CAF) can serve as alternatives to autogenous donor tissue. Additional research is needed to do the following: 1) assess the treatment outcomes for multiple-tooth recession defects, oral sites other than maxillary canine and premolar teeth, and Miller Class III and IV defects; 2) assess the role of patient- and site-specific factors on procedure outcomes; and 3) obtain evidence on patient-reported outcomes. Predictable root coverage is possible for single-tooth and multiple-tooth recession defects, with SCTG procedures providing the best root coverage outcomes. Alternatives to SCTG are supported by evidence of varying strength. Additional research is needed on treatment outcomes for specific oral sites. Clinical Recommendation: For Miller Class I and II single-tooth recession defects, SCTG procedures provide the best outcomes, whereas ADMG or EMD in conjunction with CAF may be used as an alternative.